Dignity Takings and Dignity Restoration of Indigenous Peoples in Settler Colonial Canada: A qualitative analysis of the transformative potential of free, prior and informed consent - Posselwhite, Kaitlyn (Department of Political Studies, 2019)
The ongoing reconciliation process in Canada has been criticized for failing to recognize the larger project of ongoing settler colonialism and for its inability to meaningfully respond to the aspirations and demands of Indigenous peoples for self-determination. However, in the Truth and Reconciliation Commission’s final report, the important recommendation was made for Canada to adopt the United Nations Declaration on the Rights of Indigenous Peoples, the most accomplished proclamation of Indigenous peoples’ rights, especially their right to selfdetermination, as the framework for reconciliation in the country. Following the Commission’s recommendation, the Canadian government committed itself to implementing the Declaration, including its free, prior and informed consent requirement, into the country’s legislation. This is significant for settler colonial violence in Canada continues to manifest itself in a multitude of ways, including through imposed resource extraction projects and environmental violence, which dispossesses Indigenous peoples of their land, violating their right to self-determined social, cultural and economic development, and thus, denying them their dignity. Through an application of Atuahene’s theoretical framework of Dignity Takings and Dignity Restoration, this dissertation conceptualizes eliminatory resource exploitation projects and associated environmental violence as dignity takings in a settler colonial context, whereby Indigenous peoples are dispossessed of their land, as well as their right to self-determination. It then explores the potential role the implementation of the United Nations Declaration on the Rights of Indigenous Peoples free, prior and informed consent requirement, which affirms that Indigenous people should make decisions on matters affecting their lands and/or people, can have for meaningfully restoring Indigenous peoples’ dignity, and thereby affirming their unqualified right to self-determination in settler colonial Canada. The findings demonstrate that while the free, prior and informed consent requirement’s regulatory and normative framework at the international level has the potential to meaningfully restore dignity to Indigenous peoples in theory, an assessment of the requirement’s implementation in the Canadian context reveals the considerable influence national politics and institutional norms have in shaping the requirement’s effective implementation, operationalization and dignity restoring potential.